Macrolide Resistance, Clinical Features, and Cytokine Profiles in Taiwanese Children With Mycoplasma pneumoniae Infection. (9th August 2021) - Wu, Tsung-Hua; Wang, Nancy M; Liu, Fang-Ching; Pan, Hui-Hsien; Huang, Fang-Liang; Fang, Yu-Ping; Chiang, Ting-Wei; Yang, Yu-Ying; Song, Chiah-Sing; Wu, Hsiang-Chin; Lee, Chun-Yi
Abstract: Background: The factors that predict the progression of Mycoplasma pneumoniae infection remain inconclusive. Therefore, we investigated macrolide resistance prevalence, M pneumoniae genotype, and clinical characteristics of childhood M pneumoniae respiratory tract infections in Taiwan. Methods: A total of 295 children hospitalized with respiratory tract infections with positive serological M pneumoniae immunoglobulin M test results were enrolled in this 3-year prospective study. Oropharyngeal swabs were obtained for M pneumoniae cultures and polymerase chain reaction tests. All M pneumoniae specimens were further characterized by P1 typing, multilocus variable-number tandem-repeat analysis (MLVA), and macrolide resistance genotyping. The clinical characteristics and blood cytokine profiles were analyzed accordingly. Results: Of 138 M pneumoniae specimens, type I P1 was the predominant (136 of 138, 98.6%). The MLVA type P (4-4-5-7-2) was the leading strain (42 of 138, 30.4%), followed by type J, U, A, and X. The overall macrolide-resistant rate was 38.4% (53 of 138); the resistance rate increased dramatically yearly: 10.6% in 2017, 47.5% in 2018, and 62.5% in 2019 ( P < .001). All macrolide-resistant M pneumoniae (MRMP) harbored the A2063G mutation and were MLVA type 4-5-7-2 (49 of 53, 92.5%), especially type U and X. No significant differences in clinical symptoms, duration of hospital stay, and radiographic findings were identified among patients between MRMP and macrolide-sensitive M pneumoniae (MSMP) groups. Patients with MRMP infection had more febrile days before and during hospitalization and higher interleukin (IL)-13 and IL-33 levels than patients with MSMP infection ( P < .05). Conclusions: Macrolide-resistant M pneumoniae surged in Taiwan throughout the study period, but macrolide resistance was not a determinant factor of clinical severity. Abstract : We present a 3-year prospective study on the molecular epidemiology, clinical characteristics, and cytokine profiles of childhood M pneumoniae infection in Taiwan. An increased macrolide resistance rate associated with emergence of MLVA type U was noted.